Effect of solution pH, precursor ratio, agitation and temperature on Ni-Mo and Ni-Mo-O electrodeposits from ammonium citrate baths - To, Dung T.; Park, Sun Hwa; Kim, Min Joong; Cho, Hyun-Seok; Myung, Nosang V. (Frontiers in Chemistry, 2022)
By adjusting electrolyte compositions and electrodeposition parameters, various metallic, metal/oxide composite, and oxide thin films of Ni-Mo and Ni-Mo-O were electrodeposited from ammonium citrate baths. Ni-ammonia complexes play a critical role in promoting the metallic Ni-Mo alloy depositions whose deposited Mo content increases by controlling the fraction of Ni-citrate complexes. Alkaline pH (i.e., 8-10) promotes the fraction of Ni-ammonia complexes and formation of metallic alloys, while the acidic pH results in metal/oxide composites or oxide thin films. Phase and composition were also altered by adjusting temperature, where increasing operating temperature enhanced the diffusivity of ions and reduced the concentration of Ni-ammonia complexes. Linear sweep voltammograms indicated that the electrochemical reduction of Ni is under mass transfer limit. Thus, the deposited Mo content decreased with increasing agitation.